Analisis pengaruh tingkat suku bunga, kredit macet dan capital adequacy ratio (CAR) terhadap penyaluran kredit modal kerja Bank Umum di Indonesia - Nurjanah, Rahma; Arida, Nurul (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study aims to determine and analyze interest rates on credit, bad credit, CAR, and lending to commercial banks in Indonesia. In addition, it is also to study the effect of lending rates, bad credit, and CAR on commercial bank lending in Indonesia in 2010-2018. The analytical method used in this research is descriptive quantitative. This study uses multiple linear regression analysis tools. The results of this study indicate that the interest rate, bad credit, and CAR variables simultaneously influence lending. Partially the interest rate variable has a negative and significant effect on lending. The non-performing loan variable has a negative and significant impact on credit distribution. The variable CAR has a positive and significant impact on lending. Keywords: Landing, The Interest rate on loans, Bad loans, CAR